Understanding how lake populations of arctic char are structured and function with special consideration of the potential effects of climate change: a multi-faceted approach - Budy, Phaedra; Luecke, Chris (Oecologia, 2014)
Size dimorphism in fish populations, both its causes and consequences, has been an area of considerable focus; however, uncertainty remains whether size dimorphism is dynamic or stabilizing and about the role of exogenous factors. Here, we explored patterns among empirical vital rates, population structure, abundance and trend, and predicted the effects of climate change on populations of arctic char (Salvelinus alpinus) in two lakes. Both populations cycle dramatically between dominance by small (≤300 mm) and large (>300 mm) char. Apparent survival (Φ) and specific growth rates (SGR) were relatively high (40–96 %; SGR range 0.03–1.5 %) and comparable to those of conspecifics at lower latitudes. Climate change scenarios mimicked observed patterns of warming and resulted in temperatures closer to optimal for char growth (15.15 °C) and a longer growing season. An increase in consumption rates (28–34 %) under climate change scenarios led to much greater growth rates (23–34 %). Higher growth rates predicted under climate change resulted in an even greater predicted amplitude of cycles in population structure as well as an increase in reproductive output (R ₒ) and decrease in generation time (G ₒ). Collectively, these results indicate arctic char populations (not just individuals) are extremely sensitive to small changes in the number of ice-free days. We hypothesize years with a longer growing season, predicted to occur more often under climate change, produce elevated growth rates of small char and act in a manner similar to a “resource pulse,” allowing a sub-set of small char to “break through,” thus setting the cycle in population structure.